Forgiveness is a choice a step-by-step process for resolving anger and restoring hope - Enright, Robert D. (American Psych. Assoc., 2001)
This is, "a self-help book for people who have been deeply hurt by another and are caught in a vortex of anger, depression, and resentment."
Keywords: Pardon; Perdão; Ressentiment; Vergeving; Woede; Adaptation, Psychological; Forgiveness; Hostility